Family functioning, parental cancer-related emotions, and quality of life in childhood cancer patients - Andriastuti, Murti; Fathinasari, Anisa Dwi; Arafah, Nurani Rahma; Asa, Annisa Aditya; Salsabila, Khansa; Primacakti, Fitri (Indonesian Pediatric Society, 2024)
Background Childhood cancer and its treatment affects not only children’s health, but also children’s and families’ psychosocial function, relationship, emotion, and quality of life. Several studies in developed countries have been conducted to address this issue using the Family Adaptation and Cohesion Scales (FACES) III and the Situation-Specific Emotional Reaction Questionnaire (SSERQ). Screening psychosocial problems is crucial as part of cancer comprehensive care. Objective To investigate the dynamics of family functioning, parental cancer-related emotions, and to evaluate possible associations with the child's quality of life. Methods This cross-sectional study was done in child with cancer aged 0-18 years. Parents completed the validated Indonesian versions of three sets of questionnaires regarding subjects’ quality of life (PedsQL), family function (FACES III), and family cancer-related emotions (SSERQ). Validity and reliability tests were done to assess the Indonesian versions of the questionnaires. Results A total of 269 subjects were recruited. Parental proxy of PedsQL evaluations revealed that the 8-12-year-old age group had significantly lower score than the other groups (P=0.014). Solid tumor subjects had significantly lower PedsQL score compared to subjects with hematological malignancy (P=0.001). The FACES III questionnaire results showed that connected families tended to have better PedsQL score based on children’s evaluation compared to disengaged families (P=0.049). No significant difference was found between adaptability of family function and PedsQL score. The SSERQ revealed significant associations between negative emotions and lower PedsQL scores in the children (all P=0.000). Conclusions Parental proxy of PedsQL scores were significantly lower in older children (8 to 12 years). Children with connected families have significantly higher PedsQL scores than disengaged families, for the PedsQL children’s evaluation. Parents’ emotions (loneliness, helplessness, and uncertainty) experienced by a family member of a child with cancer are also correlated with lower PedsQL scores by both evaluations.